2014
DOI: 10.15690/vramn.v69i11-12.1177
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Lipid Peroxidation – Antioxidant Protection in Perimenopausal Women with Sleep Disorders

Abstract: Objective: Our aim was to assess lipid peroxidation -antioxidant protection with the definition of the oxidative stress coefficient in perimenopausal women with sleep disorders. Methods: 45 perimenopausal women (mean age 49.1±0.32) were examined: 26 patients with sleep disorders, 19without sleep disorders. Evaluation of sleep disorders was conducted using a questionnaire of Stanford Centre for the Study of Sleep, test for assessment subjective severity of insomnia, the questionnaire for the quantitative assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…13,159 Recent study identified an evident imbalance between lipid peroxidation (LPO) and the antioxidant defense system among the menopausal insomniacs, 160 providing a pathogenic rationale for including drugs that inhibit LPO activation in the synthetical therapy of these patients. 161 A cross-sectional study involving 187 perimenopausal women also suggested that there was a positive correlation between insomnia score, menopause rating score, and LPO. 157 Acupuncture has been found to normalize disordered LPO processes, and prevent formation and accumulation of LPO products in sleep deprivation-associated regions of the brain, particularly hippocampus.…”
Section: Reduction Of Oxidative Stress Levelsmentioning
confidence: 97%
“…13,159 Recent study identified an evident imbalance between lipid peroxidation (LPO) and the antioxidant defense system among the menopausal insomniacs, 160 providing a pathogenic rationale for including drugs that inhibit LPO activation in the synthetical therapy of these patients. 161 A cross-sectional study involving 187 perimenopausal women also suggested that there was a positive correlation between insomnia score, menopause rating score, and LPO. 157 Acupuncture has been found to normalize disordered LPO processes, and prevent formation and accumulation of LPO products in sleep deprivation-associated regions of the brain, particularly hippocampus.…”
Section: Reduction Of Oxidative Stress Levelsmentioning
confidence: 97%